A cross-sectional study to examine distinct patterns of attitude towards complementary and alternative medicines (CAM) in people hypothetically facing rheumatoid arthritis. - Vats Srishti; Pandey Saksham; Raushan Kumar (Student's Journal of Health Research Africa, 2026)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune inflammatory disorder affecting 0.3-1.0% of the global population, managed through conventional, complementary, and alternative treatment strategies. Awareness and acceptance of Complementary and Alternative Medicine (CAM) among the general population remain poorly understood, particularly in relation to educational background and personal exposure to RA. This study aimed to assess CAM awareness and identify factors influencing hypothetical treatment selection for RA. Methods: A cross-sectional, mixed-methods study was conducted among 200 randomly selected participants using an online, bilingual (English/Hindi) structured questionnaire. Participants were presented with a hypothetical RA scenario and asked to select preferred treatment options among conventional, complementary, and alternative therapies. The influence of educational qualification and prior acquaintance with an RA patient on treatment selection was analyzed using Fisher's exact test. Results: Of 200 participants, 110 (55.0%) were male, and 90 (45.0%) were female; 136 (68.0%) were aged 18–30 years. Overall, 55.3% were unaware of the term CAM. Diet, physiotherapy, meditation, and yoga were among the most preferred treatment options. Educational qualification significantly influenced meditation/yoga selection (p = 0.0139), while prior acquaintance with an RA patient significantly increased selection of diet/physiotherapy (p = 0.0006) and meditation/yoga (p = 0.0026). Conclusion: Personal exposure to RA, rather than education alone, was a stronger predictor of preference for complementary, lifestyle-based therapies, underscoring the need for greater public awareness of CAM in RA management. Recommendation: The study recommends improving public awareness of CAM and its evidence-based role in RA management, particularly regarding appropriate complementary and lifestyle-based therapies.